Effect of tapered angle of a conical nose indenter on the energy absorbing variation of a copper pipe subjected to axial crushing - Shah, Qasim Hussain; ., Hanis Naily; ., Nur Syuhada (2011)
In the present research work a 100 mm long copper pipe segment with a 1 mm wall thickness is subjected to a drop weight impact by a conical shaped steel indenter with varying nose angles but constant mass. The impact velocity of the indenter was kept constant so that the kinetic energy available at impact was same for all cases. The effect of indenter nose angle from 10o to 85o was investigated with absorbed energy rising with the increasing nose angle. The problem was modeled in explicit finite element code LS Dyna. The variations in pipe folding with increasing nose angle were observed. Moreover it was found that at a particular indenter nose angle the pipe was folded onto itself which may be a helpful hint in anufacturing of straight double wall pipes.